La linterna mágica en la literatura latinoamericana (siglos XIX y XX) - Dorde Cuvardic García (Nuevo mundo - Mundos Nuevos, 2024)
The display of optical devices in the Western world was a transatlantic phenomenon, thus it also happened in Latin America. In this cultural space, magical lanterns, tutilimundis and other optical devices provided an image of the world which, at the same time, trained the spectator’s eye, as it has been pointed out elsewhere (González-Stephan y Anderman, 2006, among others). The magic lantern, in particular, was not only an important means of communication from the end of the 17th century until the beginning of the 20th century, when lost the audiences’s favors before the moving image of the cinematograph, but it was also a device represented relatively often in literary texts, among them, Latin American ones. Our interest is to study the expressive and ideological function of the magic lantern and its variants (dissolving frames, chromatrope, etc.) as a metaphor of the mind functioning and human perception in texts from José T. de Cuellar, Hilarión Frías, Heriberto García de Quevedo, José María Roa Bárcenas, Eugenio María de Hostos, Rubén Darío, Miguel Ángel Asturias, and Herrera y Reissig.